The Drosophila Gene Sulfateless Modulates Autism-Like Behaviors - Hope, Kevin A.; Flatten, Daniel; Cavitch, Peter; May, Ben; Sutcliffe, James S.; O’Donnell, Janis; Reiter, Lawrence T. (Frontiers in Genetics, 2019)
Major challenges to identifying genes that contribute to autism spectrum disorder (ASD) risk include the availability of large ASD cohorts, the contribution of many genes overall and small effect sizes attributable to common gene variants. An alternative approach is to use a model organism to detect alleles that impact ASD-relevant behaviors and ask whether homologous human genes infer ASD risk. Here we utilized the Drosophila Genetic Reference Panel (DGRP) as a tool to probe for perturbation in naturally occurring behaviors in Drosophila melanogaster that are analogous to three behavior domains: impaired social communication, social reciprocity and repetitive behaviors or restricted interests. Using 40 of the available DGRP lines, we identified single nucleotide polymorphisms (SNPs) in or near genes controlling these behavior domains, including ASD gene orthologues (neurexin 4 and neuroligin 2), an intellectual disability (ID) gene homologue (kirre), and a gene encoding a heparan sulfate (HS) modifying enzyme called sulfateless (sfl). SNPs in sfl were associated with all three ASD-like behaviors. Using RNAi knock-down of neuronal sfl expression, we observed significant changes in expressive and receptive communication during mating, decreased grooming behavior and increased social spacing. These results suggest a role for HS proteoglycan synthesis and/or modification in normal social communication, repetitive behavior and social interaction in flies. Finally, using the DGRP to directly identify genetic effects relevant to a neuropsychiatric disorder further demonstrates the utility of the Drosophila system in the discovery of genes relevant to human disease.